Religious beliefs and quality of life of the elderly in an indigenous community - Sánchez-Solano , Ma. de Jesús (Universidad de Sonora, 2022)
Introduction: The index of adult population over 60 years of age has increased remarkably globally and nationally. It could be considered that the aging of the population is a positive standard to determine the progress in the implementation of health policies, but it is also a challenge to describe the quality of life of this age group. Indigenous groups are also modified by this increase in longevity, and it is important to know how their religious beliefs affect their quality of life. Objective: Determine the relationship between religious beliefs and the quality of life of the elderly in an indigenous community. Methodology: Quantitative, correlational and cross-sectional study, with a sample of 49 elderly of both sexes, living in the community, aware of their religious beliefs and professing such religion, excluding those with mental illnesses. The SBI-15R Belief System Inventory and the WHOQOL-BREF quality of life scale were used to collect information, adhering to the provisions of the General Health Law regarding health research. Results: The mean age of the participants was 73.2 years, 55% of them reported a high quality of life and 59% a high level of religious beliefs. The correlation of the variables was statistically significant, with p=.007. Conclusions: According to this study, it can be determined that there is an association between the level of religious beliefs and the quality of life of the elderly in an indigenous community.